Macroprudential Policy : What Instruments and How to Use them? Lessons From Country Experiences. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper provides the most comprehensive empirical study of the effectiveness of macroprudential instruments to date. Using data from 49 countries, the paper evaluates the effectiveness of macroprudential instruments in reducing systemic risk over time and across institutions and markets. The analysis suggests that many of the most frequently used instruments are effective in reducing pro-cyclicality and the effectiveness is sensitive to the type of shock facing the financial sector. Based on these findings, the paper identifies conditions under which macroprudential policy is most likely to be effective, as well as conditions under which it may have little impact.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet